Evaluation of the Implementation of Integrated Pest and Disease Control by Solanaceae Farmers in South Sumatra: Evaluasi Implementasi Pengendalian Hama dan Penyakit Terpadu pada Masyarakat Petani Sayuran Solanaceae di Sumatera Selatan` - Shinta amalia Rahmadani; Bambang Gunawan; Suparman (JURNAL AGRI-TEK : Jurnal Penelitian Ilmu-Ilmu Eksakta, 2024)
Vegetables from the Solanaceae family have become a commodity that is popular with the public, however the production of these vegetables often declines due to pest attacks. Control that has a big impact on the ecosystem around the land. However, farmers still very rarely carry out integrated pest control. This research is to achieve the level of implementation of integrated pest and disease control carried out by Solanaceae plant farmers in South Sumatra. The research was conducted by surveying several Solanaceae plantations in Ogan Ilir, Banyuasin, Ogan Komering Ulu, Muara Enim, and Palembang City. The research method used was purposive sampling, which determined plant samples from each field. The research results showed that the level of IPM implementation by farmers reached a score of 61%. Although farmers generally use pesticides as the main alternative. So, farmers' application of IPM has an effect on pest and disease attacks. IPM scores affect 3% of the pest population and 46% of the percentage of disease attacks. The implementation of IPM by farmers is sufficient, so only small improvements need to be made.